Observation of manganese deposits in the Hudson Canyon by the ALVIN submersible in 1972 and 1978 and by the R/V Researcher during its COMSED expedition in 1974 - Hanselmann, D H; Ryan, William B F (PANGAEA, 1983)
During the period of 22-28 July, 1978, five dives were made in the manned submersible ALVIN into the Atlantic Ocean 3800 meter depth radioactive waste disposal site located in the Hudson Canyon channel approximately 320 kilometers from the Maryland-Delaware coast. A geological description of the site was made by direct examination of the bottom topography, bedrock exposures, sedimentary and erosional processes, and sediment cores collected from the dumpsite area. Observations within a depth range of 3985-3830 meters revealed angular blocks and piles of displaced channel wall rock, boulder and cobble olistoliths of Eocene-age chalks derived from higher elevations on the slope, and bedforms such as ripples and scour marks which imply the existence of periodic strong currents. Local benthic fauna were sparse. Three low-level radioactive waste drums were examined from the submersible, and one was subsequently recovered for corrosion, and concrete deterioration analyses. Photographic and visual evidence suggest that downslope transport of objects such as talus blocks, olistoliths, and radioactive waste drums has occurred in this area. These observations complement those made by G. Keller in earlier ALVIN dives performed in 1972 and by the AOML(MG&GL project. COMSED (Continental Margin Sedimentary Processes) cruise performed in 1974 by the R/V Researcher.